Consumer’s preferences for healthy food consumption: An empirical analysis from Mymensingh city in Bangladesh - Mahfuza, Eshrat Jahan; Hassan, Md. Fuad; Ahamed, Md. Shishir (Archives of Agriculture and Environmental Science, 2023)
Numerous non-communicable diseases are being caused by changes in food and lifestyle choices. However, the global trend of eating more healthful food is growing as people become more aware of their personal health. Nonetheless, not much scholarly work has been done on the perplexing purchasing habits of customers, especially in developing nations like Bangladesh. Hence, the purpose of this study was to determine the preference for healthy food consumption and the factors associated with consuming healthy food. The study was conducted on 140 participants selected by a purposive sampling technique from Mymensingh city. Data were collected through both face-to-face surveys and via email with the help of an e-questionnaire from May 2022 to August 2022. A five-point Likert scale was applied to assess the consumer’s preference for healthy food products. The internal consistency of the items on the scale was examined by Cronbach’s alpha. In addition, binary logistic regression was used to identify the factors that affect consumers’ decisions to consume healthy food products. The study findings provide evidence of the highly disfavored attitudes (82.86%) toward healthy food consumption among people in the study area. The analysis also reveals that factors like gender, age, education, and monthly income have a positive impact on consumption decisions, while distance from the market, occupation, family size, and credit negatively affect consumption decisions.